2017
DOI: 10.7567/jjap.56.07jf28
|View full text |Cite
|
Sign up to set email alerts
|

Control of treatment size in cavitation-enhanced high-intensity focused ultrasound using radio-frequency echo signals

Abstract: In high-intensity focused ultrasound (HIFU) treatment, controlling the ultrasound dose at each focal target spot is important because it is a problem that the length of the coagulated region in front of the focal point deviates owing to the differences in absorption in each focal target spot and attenuation in the intervening tissues. In this study, the detected changes in the power spectra of HIFU echoes were used by controlling the HIFU duration in the “trigger HIFU” sequence with the aim to increase coagula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…32) Since the size of the cavitation bubble affects nonlinear echoes, the analysis of bubble echoes may be effective for monitoring the progress of the treatment. 33) A 3P sequence may be useful for this purpose because it suppresses even the harmonic signals from nonlinear propagation. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…32) Since the size of the cavitation bubble affects nonlinear echoes, the analysis of bubble echoes may be effective for monitoring the progress of the treatment. 33) A 3P sequence may be useful for this purpose because it suppresses even the harmonic signals from nonlinear propagation. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of bubble imaging and evaluation of the acoustic field have become very important in recent years, and the role of cavitation bubbles in these studies has been examined. 21,22) In addition, we found that the hydrophone can be used for measurements in high-intensity acoustic fields even at 20 kHz frequencies. This hydrophone had a wide-frequency range receiving capability from 20 kHz up to 10 MHz.…”
Section: Introductionmentioning
confidence: 83%
“…We have been focusing research on the ultrasound imaging for HIFU treatment. [12][13][14][15] One of the problems with ultrasound imaging during HIFU treatment is that the therapeutic ultrasound components (HIFU noise) interfere with the diagnostic ultrasound components, making it impossible to monitor the tissue changes during HIFU exposure. In our previous study, [16][17][18][19] we proposed a method to remove only therapeutic ultrasound components while retaining the diagnostic ultrasound components.…”
Section: Introductionmentioning
confidence: 99%